Linking theory to practice in introductory practice learning experiences. Issue 2 (March 2015) - Fotheringham, Diane; Lamont, David; Macbride, Tamsin; MacKenzie, Laura
Abstract: Nurse educators internationally are challenged with finding a sufficient number of suitable practice learning experiences for student nurses. This paper reports on a study which aimed to evaluate the utilisation of specialised and highly technical environments ("new" environments) as first practice learning experiences for adult nursing students in the UK. A survey was conducted on 158 first year student nurses who were allocated to either "new" or "old" (those that have been traditionally used) environments. Data analysis was conducted using Mann–Whitney U test and exploratory factor analysis was performed. Results have demonstrated that all environments afford novice nurses the opportunity to observe or practice the essential skills of nursing. In addition, the "new" environments have revealed greater opportunity to observe and practice aspects of practice related to governance of care. This paper concludes that a nursing curriculum which makes clear association between the essential nature of nursing and practice based learning outcomes will help the student to appreciate contemporary nursing practice and to link nursing theory with practice. Further research is required to explain the observation that aspects of practice related to governance are more visible within highly technical areas of practice. Highlights: Novice nurses practiced nursing in all areas examined in this study. Curricular links between practice and theory foster understanding of nursing. Governance and accountability issues are more observable in highly technical areas.